OPPORTUNITY IDENTIFICATION OF NASCENT ENTREPRENEURS IN AGRICULTURAL BUSINESSES: AN EVALUATION IN SOUTHWESTERN NIGERIA (Malaysian Management Journal, 2025)
Many emerging markets in developing countries have seen a decline in entrepreneurial activity. This is especially concerning because entrepreneurs constitute a significant share of the workforce, enterprises, and national revenue. In this turbulent time of the COVID-19 crisis and its aftermath, the struggle for economic survival has added considerable pressure on the Nigerian government. Despite the economic challenges, entrepreneurs can still play a significant role in reviving the economy However, for entrepreneurship activities to take place, opportunity identification must first occur. To better understand the factors that influence the identification of entrepreneurial opportunities, this study has examined the potential effects of entrepreneurial social networks, prior knowledge, self-efficacy, proactive personality, alertness, and creativity on opportunity identification. The study employed an exploratory research design and several quantitative methods in the analysis of the collected data. The population of the study was the total number of registered nascent entrepreneurs in Southwestern Nigeria, comprising six (6) states including Lagos, Ogun, Oyo, Osun, Ondo, and Ekiti. A muti-stage sampling technique was used, while primary data was collected directly from all the participants by administering the study questionnaires. The number of questionnaires administered was 300, with a sample size of 103, which is this study’s minimum according to the Gpower result. The study found that entrepreneurial alertness and self-efficacy exhibited the strongest correlation, suggesting that entrepreneurial ability was closely linked to entrepreneurial skills. Entrepreneurial creativity and entrepreneurial self-efficacy also demonstrated a strong relationship, indicating that higher entrepreneurial skills were associated with greater entrepreneurial commitment. These variables had jointly enhanced the performance of emerging entrepreneurs in Southwestern Nigeria, highlighting the need for entrepreneurial training programs and policies that could help cultivate these abilities and characteristics. Therefore, this study has shown that opportunity identification shaped by social networks, prior knowledge, self-efficacy, proactive personality, alertness, and creativity could play a critical role in driving business sustainability by enabling entrepreneurs to recognize and exploit viable, innovative, and enduring market opportunities.